FAKTOR EKSTERNAL PENYEBAB KETERLAMBATAN MAHASISWA JURUSAN TEKNIK SIPIL FT UNP DALAM MENYELESAIKAN SKRIPSI - 949-956 , Anggia Roza (CIVED, 2016)
ABSTRACTThe aim of this study was to know external factors cause the delay of students majoring in civil engineering in finishing thesis. The design of the research is descriptive research. The population of this research is 128 students of civil engineering at faculty of engineer state university of padang. The sample is of 56 students that were taken by porposive sampling technique. Data were collected using a question naire with likert scale that used four answer choices positive and negative statements. The number of statements in the question naire were 43 point statement.The result showed that external factors cause the delay of students majoring in civil engineering in finishing thesis at the high category at 62,50 %, with details of the indicators: 1) factor family at the high category of ammounted to 44,64 %, 2) factor campus at the high category of ammounted to 73,22 %, 3) factor community at the high category of ammounted to 58,93 %, and the most dominant factor causing delay in completing the thesis is a factor campus. Keywords        : external factor, student, thesis